Anggaran Biaya Sebagai Alat Pengendalian Manajemen Pada PT Asuransi Jiwasraya (Persero) Bogor - Alfian, Dicky; Iriyadi, Iriyadi; Pramiudi, Udi (Jurnal Ilmiah Akuntansi Kesatuan, 2013)
One way to define the company's goals is to create a plan, one that cost planning is essential inthe operation of the company activity. Preparation, control, until the realization of the budget is animportant factor in the control of management. Good management control will be reflected from asound budget planning from start budgeting to realization in which the control of the use of thebudget includes the cost of the company. The purpose of this study was to determine the function ofa planning application to the realization anggarabn budget costs play an important role in themanagement control process in order to achieve the goals set previously by the company. Theresearch was conducted by the author. PT. Asuransi Jiwasraya (Persero) Bogor is located atPajajaran Street 45 Bogor. The results of this study show that the variance resulting from budgetplanning to the realization greatly affects the level of management control of the company. In otherwords, the efficiency of which is determined by the value of variance budget planning process aswell as cost control processes that will better demonstrate the value of the level of managementcontrol of the company.